Tensile Strength of Carbon Fiber/Epoxy Composite Manufactured by the Bladder Compression Molding Method at Variable Pressure Levels - Ignatius Henry Ismadi; Gesang Nugroho (Journal of Material Processing and Characterization, 2020)
Composite materials uses have been increasingly ubiquitous due to their advantages, for example, in being strong, lightweight, and rust-resistant. Various composite manufacturing processes are designed to obtain composite products of better quality, including minimizing the number of pores or voids trapped within and increasing the fiber volume fraction until an optimal value is achieved. The method employed in this research was the bladder compression molding method, and the materials used were woven carbon fabric and epoxy matrix. According to previous research which used this method, the higher the pressure in the bladder, the better the product quality generated. The aim of this research was to investigate the effect of changes in the pressure level in the bladder (1, 2, 3, 4, 5, 6, 7, and 8 bar) on the mechanical properties of the composite produced. The test specimen was gained by cutting the composite product with a CNC router machine. The tensile test results indicate that the ultimate testing tensile strength was 604 MPa and that the optimal pressure in the bladder was 7 KPa. The conclusion of this research is that the composite product quality would increase with the progressive increase in the bladder pressure to the point of optimal pressure.